Réponses

2014-03-13T20:47:34+01:00
(2x-3)(1-5x)=2x-10x^2-3+15x
13x-10x^2-3

(3x+5)(7+x)=21x+3x^2+35+5x
26x+3x^2+35

5(x+1)-2(x+2)=5x+5-2x
3x+5
Meilleure réponse !
2014-03-13T20:52:24+01:00
1)   2(x-3)-(2x+1)+3(3-2x) = 2x-6-2x-1+9-6x = -6x-2
2)  2x²+4x-3x+6 = 2x²+x+6
3)  (2x-3)(1-5x) = 2x-10x²-3+15x=-10x²+17x-3
4) 2-(x-4)+4(x-1) = 2-x+4+4x-4 = 3x+2
5) (3x+5)(7+x) = 21x+3x²+35+5x = 3x²+26x+35
6)  (4x-1)(1-3x)= 4x-12x²-1+3x=-12x²+7x-1
7)  = 5x+5-2x-4 = 3x+1
8) = 2x²-3x+10x-15 = 2x²+7x-15
9) = 6x²+4x
10) = 4x²+8x+x+2 = 4x²+9x+2
11) = -3x²+3x-2
12)3+5x-16x-32 = -11x-29
A partir du 7 je le remets plus lequation du depart mais commence dirrectement
MERCI MERCI MERCI